(untitled) (Revista científica Olimpia, 2015)
Anxiety is a special state of tension and agitation with special somatic and psychic reactions for the anticipation, memory or current experimentation of situations of insecurity or threatens, as real as imagined. Its study inside the sport environment is of significant importance for the consequences that can generate the acting of the sport activity. The article carries out a foundation on the boarding of the anxiety starting from the conception of the Cultural- Historical Focus of Vygotsky and taking as a base the Theory of the Anxiety of Martens, analyzing the components of the anxiety, from an multidimensional approach that facilitates the understanding of the phenomenon in all its extension. Are also considered many aspects that intervene in the appearance of the anxiety and their repercussion in the sport yield as well as all the elements that through their manifestations in the sportsman. It values the assumption of this theory in the evaluation of the competitive anxiety that keeps in mind the cognitive anxiety, the somatic anxiety and the self-confidence with relative independence, which facilitates the individualized attention.